Application of Translation Methods and Procedures in the Children's Storybook 《山海经》 (Shān Hǎi Jīng) - Fransiska Sella Pratiwi; Batari Andini; Tri Wahyu Retno Ningsih (Universitas Negeri Semarang, 2026)
The translation of children's storybooks is very important in bridging literature between languages and cultures. This translation not only converts one language into another, but also adapts the meaning of the message to be conveyed to the target audience. This study aims to translate a Mandarin children's storybook titled 《山海经》 (Shān Hǎi Jīng) into Indonesian using Newmark's translation method and Vinay and Darbelnet's translation procedure. The method used in this study is descriptive qualitative with observation and note-taking techniques. A total of 193 data points on the Newmark translation method and 119 data points for the Vinay and Darbelnet translation procedure were found. The most widely used method was communicative translation with 134 data, while the least used was the adaptation translation method with 2 data. For translation procedures, the most widely used was the borrowing procedure with 56 data, while the least used was the modulation procedure with 1 data.